Skills Development in a Volatile Environment: A Systems View of the Learning Process - Blair, Garry; Woodcock, Helen; Pagano, Rosane (Apex Journal of Business and Management, 2023)
Skills acquisition and development is a vital activity for society. If the latter is subject to volatile operating conditions then this activity becomes, consequentially, more difficult. The requirement to ensure the provision of an adequate supply of skilled personnel at an affordable rate is imperative. This is necessary to guarantee the delivery of services and products for society, ensuring both the level of supply and quality standards allied with development to enhance the future position. Failure in this sphere will lead to stagnation in key sectors, resulting in the decline of the society. This may impact on the technology in use and lead to comparative decline, for instance economically. The requirement to import the vital skills or purchase goods elsewhere, embodying such skills, may incur financial penalties that lead to economic decline.This paper investigates the skills development required for practice, focussing on the crucial areas of business and project management. A literature review was enacted to ascertain the main themes of the topic. This provided a framework of understanding to utilise in an empirical study. Several interviews were held with a current practitioner, who works for a company that runs international projects. These focussed on the requirements for personnel, in terms of industry demand for skills. A perspective of the current requirements, in respect of education for employability, was therefore obtained. The results are summarised using soft systems techniques, in order to highlight the potential learning in this sphere.